Calibration of a Chemistry Test Using the Rasch Model - Nancy Coromoto Martín Guaregua; Consuelo Díaz Torres; José Gilberto Córdoba Herrera; Michel Picquart (Universidad Autónoma de Baja California, 2011)
The Rasch model was used to calibrate a general chemistry test for the purpose of analyzing the advantages and information the model provides. The sample was composed of 219 college freshmen. Of the 12 questions used, good fit was achieved in 10. The evaluation shows that although there are items of variable difficulty, there are gaps on the scale; in order to make the test complete, it will be necessary to design new items to fill in these gaps.